Buck moth Hemileuca maia (Drury) - Clare Scott; Phillip E. Kaufman (EDIS)
EENY464, a 6-page illustrated fact sheet by Clare Scott and Phillip E. Kaufman, is part of the Featured Creatures collection. It describes this moth in the giant silkworm family, the larvae of which has stinging spines — synonymy, distribution, description, life cycle, hosts, and medical importance. Includes references. Published by the UF Department of Entomology and Nematology, November 2009.